A study on histopathological changes in ectopic tubal gestation - Rasheed, Fathima; Vijayaraghavan, Lilarani (International Journal of Advances in Medicine, 2022)
Background: Ectopic pregnancy is a serious cause of maternal morbidity and mortality. Fallopian tube is the most common site. Ectopic pregnancy is often the consequence of chronic salpingitis. The aim of the study was to identify the various histopathological changes in the fallopian tube, which are removed following an ectopic tubal gestation. The prevalence of various risk factors in ectopic tubal pregnancy was also investigated. Methods: This descriptive study included 160 cases of ectopic tubal gestation received in the department during the study period. Slides were studied for various changes like chronic salpingitis, acute salpingitis, salpingitis isthmica nodosa, endometriosis, tuberculosis etc. Patient’s clinical details were obtained from the medical records. Results: The most frequent pathological finding was chronic salpingitis followed by salpingitis isthmica nodosa. It was noted that all cases with a positive history of pelvic inflammatory disease (PID), showed evidence of chronic salpingitis during histopathological examination. Chronic salpingitis was also noted in 45% cases who did not give a history of PID. Among the risk factors, a history of tubal sterilization was the most frequent one. Conclusions: Even though the mortality has reduced, ectopic pregnancy causes significant morbidity and affects the fertility of women. The rise in incidence could be due to increase in prevalence of sexually transmitted diseases, increase in tubal sterilization practices and frequent use of assisted reproduction technology. It is evident from the study that many cases of PIDs are left unidentified.